Inelastic Analysis of Soil-Structure Interaction System - Al-Goraf'i, Mohammed Abdulla Ismail (2005)
Inelastic response of a framed structure is significantly different from the elastic response. Inelastic response can identify the possible locations of distress in a building as well as its failure mode. It also generates useful information such as maximum deformation, forces at important locations and the ductility requirements. Inelastic analysis of 2D frames is well reported by many researchers using either lumped plasticity models or detailed finite element models. Soil-structure interaction is another important element for a more accurate prediction of stresses in both the structure and the supporting soil. Many structural models were developed and used to solve the soil-structure interaction problems either at macroscopic or microscopic level. In macroscopic approach, Winkler model is the most popular modeling used to solve the soil-structure interaction problems. At microscopic level, finite element method is used to model both the frame structure and soil media. Most of the analyses presented in the literature focused on soil structure interaction within elastic range of loading. Very limited research focuses on the effect of nonlinearity and inelasticity of soil on the structural response.This study covers the effect of the interaction analysis on the structure inelasticity, moment redistribution and failure mode of a 2D reinforced concrete frame considering nonlinear behaviour of the soil media. The study further highlights the effect of different foundation-soil relative stiffness and the rigidity of beam-column joint on the inelastic response of the frame soil system. Finite element method integrated with stiffness matrix method is used to analyze the frame-foundation-soil system under combined vertical and lateral loading. A computer code is developed to trace the inelastic response of the frame-foundationsoil system. The developed code predicts the sequential formation of plastic hinges in the frame member and the continuous deterioration of the stiffness of the frame and soil media. The failure criteria used was based on actual nonlinear analysis of reinforced concrete section. The 2D beam element is used to model the frame members and the combined footing. The beam is assumed to retain elastic property while the inelastic property is assumed to be lumped at the ends of the beam in a form of a plastic hinge. The inelastic property is evaluated considering the actual behaviour of the reinforced concrete section, the stiffness deterioration of the frame members with the loading history, and the behaviour of the yielded section. The actual non-linear behaviour of reinforced concrete sections is carried out so that a 2D yield surface has been evolved. The formation of 2D plastic hinges in a member is based on the interaction of actual moment-axial force in the section.Plane strain Cnoded element was implemented to model the underlying soil. The stiffness of the soil was formulated using the usual finite element method. The degradation of the soil stiffness with the increase of the stress level was carried out using tangent modulus of elasticity derived from hyperbolic stress-strain model. The results indicate that the non-interaction elastic analysis underestimates the moment at different beams and columns compared to the interaction elastic analysis. Extending the analysis to the inelastic range will further significantly alters the bending moment diagrams and the percentage increase or decrease in the bending moments compared to inelastic non interaction analysis. Furthermore, the inelastic interaction analysis does not only alter the sequential formation of the plastic hinges in the frame but it will also alter the load factors at which these hinges occurs, and number of plastic hinges and their locations compared to non-interaction analysis.